TINGKAT EROSI PADA LAHAN YANG BERBATUAN DASAR BATUAN BEKU DAN BATUAN METAMORF DI DESA TAWANGREJO DAN GUNUNGGAGAJAH, KECAMATAN BAYAT, KABUPATEN KLATEN, PROVINSI JAWA TENGAH - Andi Renata Ade Yudono; Andi Sungkowo (Environmental Research Center (PPLH) of Udayana University, 2015)
The study area consists of 2 (two) landforms, the hill and the ridge. The hill and the ridge withslope varied have different rock composition, such as igneous and metamorphic rocks. Besidesthat the landcover of the two landforms also has different variety. These characteristics areexpected to affect the rate of erosion. The purpose of this study were (i) To analyze thecharacteristics of the land parameter from both landforms with different rock units, as thefactors that influence the differences in the level of erosion (ii) To determine the difference ofthe rate of erosion at the igneous and metamorphic bed rocks.Research methodology that have done were survey and mapping. The level of erosion isknown from the results of direct measurements by the method of small plots on each land unit.The survey results revealed that the rate of erosion on the rock units schist (metamorphicrocks) is greater than the unit gabbro rock (igneous). Differences in the level of erosion isinfluenced by rock units, thick soil, slope, and land use.